STRENGTHS AND CHALLENGES: SINGLE MOTHERS' RESILIENCE IN PARENTING A CHILD WITH INTELLECTUAL DISABILITY - Elsa Ofi Fitriana; Yuliana Hanami (RADJA PUBLIKA, 2025)
Being a single mother in caring for a child with Intellectual Disability (ID) is a complex challenge that involves emotional, social, and economic aspects. This study aims to understand the resilience of single mothers in facing the challenges of caring for children with ID using a qualitative phenomenological approach. This study involved a single mother participant who has been parenting a child with ID for 26 years. Data were collected through semi-structured interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The results showed that resilience of single mothers is formed through three main aspects: social support, adaptation to economic challenges, and positive coping mechanisms. The findings highlight the importance of resilience as a key factor for single mothers in navigating their complex roles. This research provides practical insights for social service providers and mental health professionals to design interventions that support the well-being of single mothers with Intellectual disability children.